CHINESE WORKERS IN MOLOTOV REGION IN THE 1950-1960: HISTORY, SOCIAL CHARACTER AND HISTORICAL MEMORY - Yang, Shusheng; Kamenskikh, M.S. (Perm Federal Research Centre Journal, 2016)
On the basis of previously unpublished sources, the circumstances of arrival, life and work of the Chinese in Molotov region in the years of 1950-1960 are reconstructed. The authors examine the socio-demographic character, reconstruct peculiarities of culture, adaptation and daily life of Chinese workers in Molotov.